2017
DOI: 10.1155/2017/6794343
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transbronchial Lung Cryobiopsies in Diffuse Parenchymal Lung Diseases: Interest of a Sequential Approach

Abstract: Background. Transbronchial lung cryobiopsies (TBLCs) are a promising diagnostic tool in the setting of diffuse parenchymal lung diseases (DPLDs). However, no comparison with surgical lung biopsy (SLB) in the same patient is available. Methods. The diagnostic yield and safety data of TBLCs, as well as the result of SLB performed after TBLCs, were analysed in a multicentric Belgian study. A SLB was performed after TBLCs in absence of a definite pathological diagnosis or if a NSIP pattern was observed without rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 22 publications
3
39
0
2
Order By: Relevance
“…Therefore, the added value of SLB performed after TBLC was evaluated in this study when the latter showed nondiagnostic or unspeci c pathological results without con dent diagnosis following another multidisciplinary discussion. Preliminary results obtained on a limited number of patients were published in 2017 [9]. In this follow up study, we provide more evidence supporting the bene t of performing SLBs in these selected situations.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Therefore, the added value of SLB performed after TBLC was evaluated in this study when the latter showed nondiagnostic or unspeci c pathological results without con dent diagnosis following another multidisciplinary discussion. Preliminary results obtained on a limited number of patients were published in 2017 [9]. In this follow up study, we provide more evidence supporting the bene t of performing SLBs in these selected situations.…”
Section: Introductionsupporting
confidence: 52%
“…Procedures were performed as previously described [9]. Brie y, all procedures were performed under general anesthesia.…”
Section: Bronchoscopy and Cryobiopsymentioning
confidence: 99%
See 1 more Smart Citation
“…Die Leitliniengruppe empfiehlt jedoch, die u.a. Aspekte der Kryobiopsie unbedingt zu beachten [141]. Kritisch anzumerken ist, dass die Prozedur bisher nicht international standardisiert ist und bisher nur wenige, teils widersprĂŒchliche Daten aus kontrollierten Studien zur TBLC im Vergleich zur chirurgischen Lungenbiopsie vorliegen.…”
Section: Empfehlungen Zur Transbronchialen Lungen-kryobiopsie (Tblc)unclassified
“…Studies comparing the diagnostic yield of transbronchial cryobiopsy and SLB in the same patient are few, and in the majority SLB was performed only when cryobiopsy results were inconclusive. Based on these limited studies, 33,41,42 SLB confirmed the diagnostic impression of the cryobiopsy in 15 of 22 patients (68%); however, the small number of cases and the selection bias are major limiting factors. Four studies have compared the diagnostic yield of cryobiopsy and SLB including 2 prospective studies 2,43 and 2 retrospective studies.…”
Section: Diagnostic Yield In Ildmentioning
confidence: 88%